Evidence of Acute Mycoplasma Infection in a Patient with Incomplete and Atypical Kawasaki Disease: A Case Report - M. Ebrahim; M. Gabay; R. F. Rivas-Chacon (Case Reports in Medicine)
The etiology of Kawasaki disease remains unknown despite extensive studies. Some researchers suggest that it is caused by an infectious agent. This is a case report where a patient with incomplete Kawasaki disease was found to have evidence compatible with acute Mycoplasma pneumoniae infection. This is one of the several case reports linking Mycoplasma pneumoniae to Kawasaki disease as a possible trigger. This is perhaps due to a superantigen or is mediated by some other mechanism. Accurate and timely testing for Mycoplasma infections is difficult and has its limitations. Despite this, Mycoplasma pneumoniae should be considered in the differential and workup for Kawasaki disease.